HYDROPROCESSING OF GASOLINE AND DIESEL FRACTIONS ON MODIFIED ALUMO-NICKEL-MOLYBDENUM CATALYSTS - Tuktin Balga Tuktiyevich; Shapovalova Larisa Borisovna; Abilmagzhanov Arlan Zainutallaevich; Shamshat Nurbek Auesbayuly (Academic Scientific Journal of Chemistry, 2019)
The paper presents the results of the study of hydroprocessing of gasoline and diesel oil fractions on alumina catalysts modified with variable valence metals, additives of phosphorus and lanthanum. The process of hydroprocessing gasoline and diesel fractions was studied in a high-pressure flow installation with a fixed catalyst bed at temperatures of 320-400°C, pressure 2.5-4.0 MPa and flow rate of the feedstock 1-3 h-1 . The results obtained in tests of catalysts in the process of hydroprocessinggasoline and diesel oil fractions show that the greatest hydrodesulfurization activity is observed at a temperature of 380-400°C, a pressure of 4.0 MPa and a flow rate of 1 h-1 . Under optimal conditions, during the processing of straight-run gasoline fraction, the highest octane number is characteristic of the KGO-21 catalyst (NiO-МоO3-La2О3-Р2О5-ZSM-Al2О3): 91.8 (RM) and 72.4 (MM). The KGO-23 catalyst (NiO-МоO3-La2О3-Р2О5-ВЕА-Al2O3) has a high hydroabsorbing activity. After hydroprocessing of straight-run gasoline and catalytic cracking gasoline, sulfur was not detected on this catalyst. When hydroprocessing the diesel fraction of oil, the lowest pour point and cloud point of diesel fuel are achieved on the KGO-21 catalyst: minus 58.9 ° C and minus 57.7 ° C, respectively. Diesel fuel produced on this catalyst contains the least amount of residual sulfur compared with other catalysts. By the method of temperature-programmed desorption of ammonia, it was found that the concentration of acid sites on the KGO-21 catalyst is 31.3 • 10–4mol NH3des / g cat. On the surface of the KGO-23 catalyst, two forms of adsorbed ammonia were found with a Tdes = 175 and 220 ° C (10.2 and 9.5 molNH3des / g cat, respectively). The total amount of NH3des = 19.7 • 10-4molNH3des / g cat. The KGO-21 catalyst has the highest concentration of acid sites, which determines its high hydroisomerizing activity in the hydroprocessingof gasoline fractions.